DETERMINATION OF MINERAL CONTAIN AND BACTERIA CONTAMINANT ON ORGANIC AND NONORGANIC FRESH VEGETABLES - Harsojo Harsojo; June Mellawati (Indonesian Journal of Chemistry, 2009)
The determination of mineral content and bacteria contaminant on fresh vegetable of long bean (Vegan ungulate Wall.), white cabbage (Basic tolerance L.), and lettuce (Lectuca sativa L.) that cultivated by organic and nonorganic system have been done. The mineral content has been analyzed using neutron activation analysis and atomic absorption spectroscopy method, while bacteria contaminant by total plate count number using Nutrient Agar, Mac Conkey Agar, Baird Parker medium, and Salmonella using selective medium. The results showed that there are some essential mineral such as Fe, Zn, Ca, Co, and nonessential mineral Cd. There is tendency that fresh vegetable that cultivated by organic system contained Fe, Zn, Ca, Co and Cd mineral less than nonorganic. The Zn mineral content in nonorganic of fresh vegetable were higher than the limit of threshold number from Health Department, Republic of Indonesia (2004), while Cd mineral in organic or nonorganic of fresh vegetable were greater then threshold number from Codex Alimentarius Commision. The measurement of bacteria contaminant on organic and nonorganic of fresh vegetables contained aerob, coli, and Staphylococcus bacteria in organic of fresh vegetables were less compared to nonorganic of fresh vegetables.